PENERAPAN MANAJEMEN RISIKO KEBAKARAN DI AREA PRODUKSI PT WILMAR BIOENERGI INDONESIA KAWASAN INDUSTRI DUMAI– PELINTUNG TAHUN 2015 - serani -; lina tarigan; isyatun mardiyah syahri (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Fire is an incident that is undesirable and should be considered in any kind of industrial production activity. PT Wilmar Bioenergi Indonesia Kawasan Industri Dumai- Pelintung is a company which is the field RPO (Refined Palm Oil) become biodiesel processed has a risk of fire and the explosion which require a fire risk management. The purpose of this study to determine the implementation of fire risk management at biodiesel production area. The research is a descriptive study using a qualitative approach. Informan in this study consist one informant from Top management, one informant from Environment, Health, and Safety (EHS) Department, one informant from Electric and Instrument (E & I) Department, and one informant from Biodiesel Production Department. Method of collecting informations is through interviews, observation and document review, then will be analyzed with conten analysis method and the data are presented in narrative form. The result showed management polices committed to creating a healthy working environment and disseminated to all employees through simulated fires. The company has also set rules to control the source of fire and flammable material. Education and training has been given to employees regularly 2 up to 3 times a year. Installation of fire protection systems according to international standards National Fire Protection Association (NFPA) and routine inspection once per- month. The investigation and reporting of fire have existed and documented on the EHS’s department and in 2013 the audit done internally. It is recommended that the implementation of fire prevention and control to be maintained and improved both concerning human resources and facilities which contribute to implementation of risk management, held fire risk appraisal and improving surveillance towards any kind of fire risks. Keywords: Fire Risk Management, EHS, NFPA, Management Policy.